Photoinactivation of extensively drug-resistant gram-negative bacteria from healthcare-associated infections in Venezuela - El Hindawi, Gamal; Varela-Rangel, Yasmín Yinec; Araque, María (International Journal of Research in Medical Sciences, 2023)
Background: The overwhelming advance of antimicrobial resistance demands the incorporation of new antibiotics and effective alternative treatments, and among the latter, blue light phototherapy. The objective of this study was to evaluate the photoinactivation effect of irradiation with blue light (405 nm) on extensively drug-resistance (XDR) Gram-negative bacteria from healthcare-associated infections Methods: A lighting unit was made using a 50W LED fitted to a condenser lens to create an irradiance gradient. After characterization of the lamp and standardization of microbiological procedures, bacterial inocula of 1.5×107 CFU of 40 bacterial strains: 27 Enterobacterales and 13 Pseudomonadales were subjected to irradiation for 15 minutes with blue light. The results were analysed with the SPSS program and by applying the Shapiro-Wilk and Mann-Whitney tests. Survival rates were also calculated. Results: 82.5% of the strains were photoinactivated, with inhibition thresholds between 86 and 126 J/cm2 for most of the Enterobacterales and below 86 J/cm2 in large part of the Pseudomonadales, these being the most sensitive group. 17.5% of the strains showed tolerance to irradiation thresholds up to>171 J/cm2. The survival rate decreased as the halo of inhibition of bacterial growth increased. The photoinactivating effect of blue light on the bacteria studied was a characteristic independent of the complexity of the resistance pattern that these strains presented. Conclusions: The findings obtained show that blue light has an important photoinactivating effect against XDR Gram-negative bacteria of nosocomial origin and can be considered as a future therapeutic alternative to contain the phenomenon of antimicrobial resistance.